Gender Inequality in Precarious Academic Work: Female Adjunct Professors in Italy - De Angelis, Gianluca; Grüning, Barbara (Frontiers in Sociology, 2020)
International research studies and national reports point out two specific aspects which characterize women’s academic careers (cf. Eagly 2004; Glass and Cook 2016). First, few women advance to senior academic roles. Second, although female academics progress in numbers equivalent to their male colleagues up to a certain point, in most cases their academic career paths either stop before they arrive at tenured positions or they remain in the lower ranks of the hierarchical academic structure. Thus, while the numeric growth and temporal extension of fixed-term positions has, overall, increased women’s opportunities for researching and teaching at universities, on the other hand, it has impeded their access to tenured positions. To better highlight this dynamic, this article focuses on the situation of female adjunct professors in Italy. The interest in adjunct professors is twofold: on the one hand, the social and economic status of adjunct professors in the Italian academic system have worsened over time, from independent to formal independent workers; on the other hand, compared with other non-tenured positions, there are substantially fewer female adjunct professors than male. We first provide an overall picture of the historical and juridical transformations of the rank distribution of faculty in Italian universities from the perspective of gender. As a second step, we compare the actual working conditions of female and male adjunct professors on the basis of a survey carried out from January to October 2018 (5,556 respondents corresponding to more than 20% of the population) and semi-structured interviews with 31 adjunct professors. The aim of the analysis is to pinpoint objective and subjective gender similarities and differences regarding both socio-economic variables and the ways male and female adjunct professors think about their academic and extra-academic work; how they experience the academic environment between paid and unpaid work, construct their professional/academic identity, and imagine their professional future and perceive problems related to the administration and organization of their academic work.